A journey to HIV prevention research: From social psychology to social health via multidisciplinarity. (March 2018) - Kippax, Susan
This is a personal account of my research in HIV prevention from 1984 to the present day. It demonstrates my disquiet with the individualism of psychology as a way of thinking about what was needed to prevent HIV transmission. HIV prevention requires social transformation which is produced via changes in social practices and norms of communities and networks rather than by changes in behaviours of individuals. My colleagues and I developed a 'social health' model of social transformation that involves enabling communities to modify their social practices by building on emergent community responses, responses that were identified by the use of a reflexive research methodology.